Entscheidungsprozesse zur Anpassung an den Klimawandel in Kommunen. - (:unkn) unknown (My University, 2015)
Zentrale Bausteine des Berichts sind eine Literaturauswertung und eine empirische Untersuchung zu Anpassungsprozessen in Kommunen und kommunalen Einrichtungen. Der Fokus der Analyse liegt dabei auf den Anstößen und Hindernissen zur Auseinandersetzung mit der Thematik sowie auf den verschiedenen kommunalen Ansätzen zur Umsetzung von Anpassungsmaßnahmen. Die Untersuchungen zeigen, dass unter anderem die eigene Betroffenheit durch Extremwetterereignisse, Teilnahme an Forschungsprojekten und Förderprogrammen sowie passende Schnittstellen mit dem Klimaschutz häufige Einstiegspunkte zur Auseinandersetzung mit Klimafolgen in Kommunen darstellen.

The present study will lay the scientific foundation for updating the "Klimalotse", an online manual, which helps organisations adapt to climate change in Germany. A literary analysis and an empirical examination of the adaptive processes in municipalities and municipal establishments form the core components of this study. The analysis focuses on the incentives for and barriers on dealing with this issue, as well as the various municipal approaches for implementing adaptive measures. The results show that factors including the impact of extreme weather events, participation in research projects or funding programs, and interests that overlap with climate mitigation issues each present municipalities with several opportunities for beginning to deal with the effects of climate change. Moreover, municipal administrators view the scarcity of resources, the lack of political or managerial support and the insufficiency of current data sources as limiting factors to their work. The concluding find-ings gleaned from the revision of the climate guide are compiled in a brief summary. This information, together with an evaluation of the online manual and an analysis of key studies on risk communication, will lay the foundation for a subsequent analysis of the Klimalotse. The evaluation will be carried out in three ways: through a workshop with the climate guide s target group (representatives from municipal management), an internal laboratory test of the system, and an evaluation of users access data from the online manual s webpage. Lastly, the main findings of the study will be put together into a proposal that aims at further improving this online tool.
Keywords: Kommunalpolitik; Verwaltungshandeln; Klima; Umweltschutz; Kommunaler Klimaschutz; Klimaanpassung